Respon Pertumbuhan dan Hasil Tanaman Cabai terhadap Aplikasi Pupuk Cair Organik dengan NPK pada Inceptisol Jatinangor - Eso Solihin; Rija Sudirja; Anni Yuniarti; Nadia Nuraniya Kamaluddin (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACT This study aimed to determine the effect of the application of liquid organic fertilizer (PCO) accompanied with Nitrogen-Phosphate-Pottasium (NPK) fertilizer towards the growth and yield of chili plants on Jatinangor Inceptisol. The study was conducted from September 2017 until January 2018 in the experimental field and Laboratory of Soil Chemistry and Plant Nutrition, Faculty of Agriculture, Universitas Padjadjaran. The experimental design used was simple Randomized Block Design consisted of 10 treatments. Each treatments were repeated 3 times with the treatment arrangement as follows; A: Control 0 PS + 0 NPK, B: 0 PCO + 1 NPK, C: 1 PCO + 0 NPK, D: 1 PCO + ¼ NPK, E: 1 PCO + ½ NPK, F: 1 PCO + ¾ NPK, G : 1 PCO + 1 NPK, H: ¼ PCO + ¾ NPK, I: ½ PCO + ¾ NPK and J: ¾ PCO + ¾ NPK. The results showed that the treatment with the highest yield was treatment F, which is 1 dose of PCO or 4 liters per ha of PCO together with a dose of NPK or 112.5 Urea, 150 SP-36 and 112.5 KCl yielded an average 333.76 grams of fruit per plant. Key word: Chili, NPK, PCO, Yield